2009
DOI: 10.1016/j.jmb.2009.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Structures for 5′ Regions of R2 Retrotransposon RNAs Reveal a Novel Conserved Pseudoknot and Regions that Evolve under Different Constraints

Abstract: SummarySequences from the 5′ region of R2 retrotransposons of four species of silk moth are reported. In Bombyx mori, this region of the R2 messenger RNA contains a binding site for R2 protein and mediates interactions critical to R2 element insertion into the host genome. A model of secondary structure for this RNA fragment is proposed on the basis of binding to oligonucleotide microarrays, chemical mapping, and comparative sequence analysis. Five regions of conserved secondary structure are identified, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
72
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 46 publications
2
72
0
Order By: Relevance
“…In addition, we incorporated 2Ј-OMe substituents on all of the RIPtides displayed on the microarray (Fig. 1, A and B), a modification known to increase oligonucleotide affinity for RNA targets (42,43) as well as stability toward nucleolytic degradation; this modification has previously been used by Turner and co-workers (13)(14)(15)(16)(17)(18) to increase the resolution of RNA structure-mapping by microarray screening.…”
Section: Journal Of Biological Chemistry 18845mentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we incorporated 2Ј-OMe substituents on all of the RIPtides displayed on the microarray (Fig. 1, A and B), a modification known to increase oligonucleotide affinity for RNA targets (42,43) as well as stability toward nucleolytic degradation; this modification has previously been used by Turner and co-workers (13)(14)(15)(16)(17)(18) to increase the resolution of RNA structure-mapping by microarray screening.…”
Section: Journal Of Biological Chemistry 18845mentioning
confidence: 99%
“…Of particular note in the latter regard is the work of Turner and colleagues (15)(16)(17)(18), who employed microarrays of 2Ј-OMe ribonucleotides and locked nucleic acids to perform an independent experimental assessment of the predicted secondary structure for several biologically relevant RNAs. Efforts along these lines to date have involved sparse sampling of ligand sequence space, with at most 320 candidate sequences examined per study, these having been designed on the basis of Watson-Crick complementarity to prospective docking sequences on the RNA target of interest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further support for this model is the lack of a conserved initiation codon upstream of the identifiably conserved R2 ORF. 5 In silkmoth R2 28S-R2 co-transcript. Comparisons of possible secondary structures to the five known classes of self-cleaving ribozymes revealed that R2 RNA has remarkable similarities to the hepatitis delta virus (HDV) ribozyme (Fig.…”
Section: Overviewmentioning
confidence: 99%
“…The location of this structure and the utilization of RNA pseudoknots as internal ribosome entry sites (IRES) for some viral RNAs 6 suggests that this structure is important for R2 protein synthesis. 5 The R2 RNA interacts with the R2 protein during insertion into the host genome. The mechanism by which the R2 element inserts has been well documented for Bombyx mori and proceeds via an ordered sequence of DNA cleavage and synthesis.…”
Section: Rna Structuresmentioning
confidence: 99%